2019
DOI: 10.1016/j.scitotenv.2018.12.233
|View full text |Cite
|
Sign up to set email alerts
|

Modelling environmental antibiotic-resistance gene abundance: A meta-analysis

Abstract: The successful treatment of infectious diseases heavily relies on the therapeutic usage of antibiotics. However, the high use of antibiotics in humans and animals leads to increasing pressure on bacterial populations in favour of resistant phenotypes. Antibiotics reach the environment from a variety of emission sources and are being detected at relatively low concentrations. Given the possibility of selective pressure to occur at sub-inhibitory concentrations, the ecological impact of environmental antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 58 publications
1
15
1
2
Order By: Relevance
“…Class 1 integron is a potentially mobile genetic element, commonly found in Gram-negative bacteria, responsible for the conjugative-mediated gene transfer [9]. Thus, in both marine and terrestrial environments, wildlife can come into direct contact with most antibiotics, even at sub-inhibitory concentrations [10], leading to the selection of antibiotic-resistant microbiota. In this context, wildlife represents a potential reservoir, or vector, of resistant pathogens and ARGs [1,11,12]; therefore, in the study of the spread of the AMR, it may be useful to evaluate the role of migratory wildlife species, which can carry a resistant microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Class 1 integron is a potentially mobile genetic element, commonly found in Gram-negative bacteria, responsible for the conjugative-mediated gene transfer [9]. Thus, in both marine and terrestrial environments, wildlife can come into direct contact with most antibiotics, even at sub-inhibitory concentrations [10], leading to the selection of antibiotic-resistant microbiota. In this context, wildlife represents a potential reservoir, or vector, of resistant pathogens and ARGs [1,11,12]; therefore, in the study of the spread of the AMR, it may be useful to evaluate the role of migratory wildlife species, which can carry a resistant microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…We further compared the frequency of samples positive for tetB , tetX , sul1 , sul2 , and int1 , and the copy number of tetX , sul1 , and int1 as it was reported that the copy number of resistance genes correlates with antibiotics concentration in drinking water and hydroponic vegetables [ 17 , 27 ]. A meta-analysis also suggested that antibiotic selection pressure, as a function of antibiotic concentration, is positively correlated to the abundance of antibiotic resistance gene [ 28 ]. The copy number of sul1 was consistently higher than that of tetX in all three groups, suggesting that all the produce may be exposed to a higher concentration of antibiotics of sulphonamide class.…”
Section: Discussionmentioning
confidence: 99%
“…The copy numbers of ARGs based on CT were calculated by application of comparative CT method [14]. The absolute abundances of the target ARGs and intI1 were calculated as follows [15,16]:…”
Section: Plos Onementioning
confidence: 99%